Tingkat Pengetahuan Dan Praktik Penjamah Makanan Tentang Hygiene Dan Sanitasi Makanan Pada Warung Makan Di Tembalang Kota Semarang Tahun 2008 - Budiyono, Budiyono; Isnawati, Isnawati; Wahyuningsih, Tri (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: Foods and beverages are potentially contaminated by pathogenic microorganism and chemical agent. As a centre of education area, Tembalang has many food courts which unfortunately, the food handlers’ knowledge on hygiene and food sanitation is lacking. Basedon Ermayani’s finding, the sanitation level of pecel/food handlers in Sumurboto and Tembalang was below the quality of standard Permenkes No.715 about Hygiene and Food Sanitation Requiremants. This study aims to describe and to analyze the level of knowledge and practice of food handlers in hygiene and food sanitation.Method: It was a cross sectional study employed observational method involved 36 nasi rames handlers in Tembalang.Result:. The study found that respondents’ level of knowledge were mostly poor (63,9%). whilst, the level of practice was mostly good (77.8%). Keyword : Knowledge, Practice, Hygiene and Food Sanitation, Nasi Rames Handler.